Copyright Law Analysis Related to the Use of Artistic Image Works in Artificial Intelligence Training Data in Indonesia and Singapore - Lintang Akbar Samudra; Yudho Taruno Muryanto (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The emergence of Artificial Intelligence presents a challenge in Copyright law in the context of visual artworks, as various Artificial Intelligence systems are currently available to create images. Based on this, the research aims to examine the legal regulations regarding the use of Artistic Image Works in Artificial Intelligence training data according to the Copyright Laws of Indonesia and Singapore, as well as how Copyright regulations can be developed to address these legal issues. This study uses a normative legal research method with a descriptive nature, employing statutory and comparative approaches. The data consists of secondary legal materials, collected through library research and analyzed using a syllogistic method with deductive reasoning. The findings and discussion of this research reveal that there is currently no clear legal basis for the use of Artistic Image Works in Artificial Intelligence training data under Law Number 28 of 2014 on Copyright in Indonesia, whereas the Singapore Copyright Act 2021 has accommodated this issue through provisions on Fair Use and Computational Data Analysis. Therefore, a reformulation of regulations is needed regarding several aspects such as Use, Reproduction, and the role of Collective Management Organizations.